Multiple faces of narcissistic leadership in Medical Education - DINESH KUMAR V (Journal of Advances in Medical Education and Professionalism, 2019)
Narcissism, being the critical part of the toxic leadership paradigm,has its own impact in the education sphere. Contrastingly,leader’s narcissism cannot be simply underweighted because suchleaders often tend to be creative strategists who can take riskychallenges to suffice the self-ego and leave behind a legacy aswell. This commentary intends to portray the complex mosaic ofthe positive and negative consequences inbred in a narcissisticleader. The debate over whether these people provide a net gain orloss remains everlasting because it varies based on the organizationalclimate and also other contextual factors.